(untitled) (City: History, Culture, Society, 2020)
This article aims to demonstrate the key transformations that took place at the Holocaust sites in the Dnipro (former Dnepropetrovsk) from the end of the Nazi occupation to the present day. It explores the extent to which these locations have become places of the Holocaust commemoration and describes the mechanisms and features of inclusion of such commemoration into the city’s urban space. The author analyzes the main initiators and supporters of the Holocaust commemoration in order to evaluate how effectively the history of the extermination of Jews is represented in urban space of Dnipro and how much it corresponds to its contemporary image. The article, based on existing historiography, describes events in the three main locations of the Holocaust in Dnepropetrovsk (Dnipro), where the most large-scale acts of the extermination of the Jewish population took place – near the Botanical Garden (Krasnopovstanska Balka), the Jewish Cemetery (Park of Pisarzhevsky), the village of Verkhnie (the intersection of Yangel and Energeticha streets. Sufficient body of research provides fairly reliable evidence of what took place in the aforementioned locales during the Nazi occupation. An important feature that subsequently influenced the commemoration of these places in both the Soviet and the post-Soviet periods was that in the first location, i.e. in the Krasnopovstanska Balka (ravine), those executed were exclusively Jewish, while in the other two locations, different categories of Nazi victims were executed, including a significant number of Jews. In the 1960-1980s, a period of honouring the history of the Great Patriotic War, monuments, erected to commemorate the victims, only bore inscriptions, typical for the Soviet officialdom. These inscriptions did not mention the ethnic origin of Jewish victims, dissolving them in euphemistic formulations, such as “civilians”, “Soviet citizens”, etc. After the collapse of the USSR, old taboos were lifted and previously forbidden historical facts and narratives, including the identity of national groups claiming their place in historical consciousness began to take shape. This article analyzes various combinations of memorial discourses – Soviet and Jewish / Soviet and post-Soviet / Jewish, Soviet and Ukrainian – and how they relate (interact / conflict / do not communicate) in the mentioned locations. Based on her analysis, the author concludes that the city’s Jewish community was the main initiator and supporter of the preservation of the Holocaust memory, which has led to the high degree of fragmentation of the commemoration of the Holocaust in Dnipro. Nevertheless, thanks to the collaboration and occasional joint activities of Jewish organizations, as well as Dnipro’s public and governmental institutions, the memory of Holocaust has become gradually incorporated into the urban space, where it occupies a more prominent place.